Perspectives on the treatment of the longitudinal spinal cord injury - Thomas Carlstedt (Frontiers in Neurology, 2010)
Abstract The current technique for surgical treatment of the longitudinal spinal cord injury has proven to be successful for restoration of some motor function and alleviation of pain. This has been the first step in finding a cure for spinal cord injuries, but so far there are many obstacles still to be overcome. In this particular injury return of function from spinal cord surgery is only partial. Some of the main remaining problems are related to injury induced neuronal death, direction and specificity of regeneration and muscle and receptor disintegration from long time denervation. Currently this is a surgical procedure without any adjuvant treatments. In order to gain further functional improvement combinational therapies developed in basic science experiments are essential.